Política de isenção do ICMS e do IPVA na aquisição de veículos para pessoas com deficiência na cidade de Fortaleza: uma avaliação crítica - Oliveira, Josival Conrado de (2022)
The present dissertation, entitled: ICMS and IPVA Exemption Policy in the Acquisition of Vehicles for People with Disabilities in Fortaleza City: A Critical Assessment aims to analyze and evaluate the scope of public policy and its possible benefits in favor of people with physical, hearing, mental, visual and autism disabilities in the city of Fortaleza, guided by an inclusive concept, guarantor of rights and grounded in the exercise of citizenship and fundamental human rights. The main focus of the research was to listen to people linked to social movements for the defense of people with disabilities, people linked to dealerships that sell ICMS and IPVA exempt vehicles, people who participate in CONFAZ, policy management at SEFAZ and people with the aforementioned disabilities. The meaning of this listening aimed at the knowledge and evaluation of people with disabilities assisted by the public policy under study, that is, listening to opinions, criticisms and suggestions taking into account the reality experienced by them, the cultural, social and economic aspects in which they are inserted. It was in this perspective that the research was developed, considering the time frame from 2014 to 2018. Thus, we opted for a mixed research model: qualitative based on the interpretive-comprehensive paradigm, defended by Rodrigues (2008), with open interviews and in the positivist paradigm, defended by Gil (2021), with a quantitative bias in the descriptive research and with the application of questionnaires that theoretically contemplated the main categories analyzed, such as: equity, equality and social justice, according to the thinking of the authors that were cited, who gave us theoretical support, in addition to the opinion of those surveyed. Based on the information from the questionnaires and the interviews carried out, the analysis of the policy sought to identify the successes that provide benefits to the user of the policy, as well as the points of obstacles that make it difficult for people with disabilities to access the tax benefit. In this sense, the premises initially raised, as well as the hypotheses raised, were confirmed in the aspect of the positive evaluation of most of the respondents who recognized the benefits and social reach brought by the researched policy, however, pointing out the critical aspects that make it difficult or even prevent people with disabilities from accessing the policy under analysis.